Discricionariedade e princípios na hipermodernidade - Banhos, Sérgio Silveira (2007)
This thesis addresses the recent doctrinal and jurisprudential tendency observed in the law in the context of hypermodernity, which indicates an effective reduction in the use of discretionality in administrative acts as a result of the integrated ap-plication of principles and rules. The traditional legalistic approach is currently giv-ing way to a more wide-ranging view, exemplified in Ronald Dworkin s theory of law as integrity through which not only rules, but also principles themselves, should be subjected to a systemic, integrated analysis. Given this, Dworkin s work forms the theoretical platform for the questions raised by this entire study, since the integrated application of principles and rules has become fundamental in the pursuit of the ideal of justice, bringing a new focus on the role of administrative law in an environment of deep and rapid change that typifies hypermodernity. Consid-ering the new concept of the separation of powers, the notion of strict legality, by presupposing a means of controlling the exercise of State power, must be set against other constitutional principles of equal importance, taking into account the particularities of each case in question. In this context, the traditional concept of discretionality is outmoded. Jurisdictive control of these acts is not only possible, but also absolutely essential in a democratic state of law. The synthesis of this new paradigm for administrative law is clear and should be an indissoluble part of administators agenda in contemporary society: citizens are the effective benefici-aries of constitutional rights and guarantees. The technique of balancing principles by assessing their values in the particular case is already part of the jurisprudence of hypermodernity, which is in synchrony with neopositivism and the theory of law as integrity